The Problem of Transforming Pagan Temples into Christian Churches. The Case of North-Palestinian Architecture of Late Antique Period - Tarhanova, Svetlana V. (Actual Problems of Theory and History of Art, 2014)
The problem of transformation of pagan temples into Christian churches is one of the most actual problems in contemporary European historiography. In my work it is shown on the example of Palestinian architecture. The historical references on such transformations (Jerusalem, Gaza) have been united with archeological evidence (North-West church in Hippos-Sussita, church of Saints Cosma and Damian in Dor, churches in Sepphoris, Beth Shean, Omrit and hypothetically in Nazareth, Tabgha and Evron). These processes were not necessarily accompanied by conflicts. More frequently Christian churches were built at the foundations of already abandoned temples. That’s why the conception of antagonism between religions, based only on the historical references, seems to be exaggerated (5–6 cases). Only in Northern Palestine there were approximately 40 temples, 120 churches, 70 synagogues. And all of them peacefully coexisted during a long period while paganism gradually faded out. Temples were one of the most important source for architectural forming of the Christian basilica that is shown by examples of direct adoptions of fundaments and architectural details during the rebuilding.
Keywords: Palestine; Late Antiquity; temples; Christian churches; transformations; antagonism; religious and archaeological adoptions; genesis of Christian basilica